answersLogoWhite

0


Best Answer

(7+5) - (8-3) = 7



proof:-

(12) - (5) = 7

User Avatar

Wiki User

11y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: Where would the parentheses go in 7 plus 5 minus 8 minus 3 equals 7?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

Minus 2 parentheses w minus 7 parentheses plus 10w equals 34?

-2w+14+10w=348w=20w=2.5


Where would you put parentheses around the following equation 200 minus 90 plus 20 equals 10?

(200-90)+20=10


What is a plus equals plus plus a minus minus minus a?

Your question does not make sense. It would probably be interpreted as a + = ++a ---a


What are commonly used math symbols?

= equals + plus - minus × time ÷ 0mj %percent () parentheses > greater than < less than


What is the answer to parentheses 43 minus 19 parentheses plus parentheses 16 minus 14 parentheses parentheses 4 parentheses and how did you get the answer?

(43 - 19) + (16 - 14)(4)= 24 + (2)(4)= 24 + 8= 32


What is 2.3 plus in parentheses 4.5 minus 2.1 parentheses?

Just take the parenthesis and you will have your answer.


Whats the factor from of 2xy-4x plus 8y-16?

2xy - 4x plus 8y - 16 equals x plus 4 in parentheses multiplied by 2y minus 4 in parentheses. So, the factors are ( x + 4) and ( 2y - 4) .


What is twenty four divided by two eight minus three parentheses six minus two parentheses plus one equals?

(24/2)*8-3*(6-2)+1 = (12*8)-(3*4)+1 = 85


Does plus minus mean plus?

Same mathematical signs equal plus Different mathematical signs equal minus Plus Plus = Plus (+)(+) = + Minus Minus = Plus (-)(-) = + Plus Minus = Minus (+)(-) = - Minus Plus = Minus (-)(+) = - So the direct answer to your question would be: plus minus equals minus


1316 minus parentheses 1416 plus 316 parentheses?

1316 - ( 1416 + 316 ) = - 416


Where would you put parentheses around the following equation using the order of operations to make it true 13 plus 7 minus 6 plus 4 times 2 equals 0?

13 + 7 - (6 + 4) * 2 = 0


Where would you put parentheses around the following equation using the order of operations to make it true 6 minus 3 times 7 plus 4 equals 33?

It is: (6-3)*(7+4) = 33